Carbazolylphosphines and carbazolylphosphine oxides: facilely synthesized host materials with tunable mobilities and high triplet energy levels for blue phosphorescent OLEDs. Issue 29 (17th July 2017) - Zhao, Zifeng; Yu, Gang; Chang, Qiaowen; Liu, Xiaochen; Liu, Yang; Wang, Liding; Liu, Zhiwei; Bian, Zuqiang; Liu, Weiping; Huang, Chunhui
Abstract : Selectively modulating the charge mobility of host materials by the oxidation of phosphines for highly efficient blue phosphorescent OLEDs. Abstract : A high triplet energy level ( E T ) and balanced carrier mobility are critical factors for host materials in efficient blue phosphorescent organic light-emitting diodes (PHOLEDs). Herein, we report a facile synthesis of four compounds, dicarbazolylphenylphosphine (DCPP ), dicarbazolylphenylphosphine oxide (DCPPO ), tricarbazolylphosphine (TCP ), and tricarbazolylphosphine oxide (TCPO ), and their application as host materials in a classic blue phosphorescent emitter bis[2-(4, 6-difluorophenyl)pyridinato- C 2, N ](picolinato)iridium(iii ) (FIrpic). The four compounds show a high E T of up to 3.0 eV and tunable mobilities. We fabricated four OLEDs with a device structure of ITO/MoO3 (1 nm)/ N, N ′-dicarbazolyl-3, 5-benzene (mCP):MoO3 (20 wt%, 10 nm)/mCP (30 nm)/Host:FIrpic (7 wt%, 20 nm)/1, 3, 5-tri( m -pyrid-3-yl-phenyl) benzene (TmPyPB, 40 nm)/LiF (1 nm)/Al (100 nm), all of which display maximum external quantum efficiencies (EQEs) exceeding 20%. TheDCPPO -based device reaches the highest EQE of 27.5%, the maximum luminance of 14 070 cd m −2, and the lowest efficiency roll-off of 22.2% from 1 to 10 mA cm −2, which is among the best-performing FIrpic-based PHOLEDs without using any light extraction method.